2019
DOI: 10.1111/sdi.12834
|View full text |Cite
|
Sign up to set email alerts
|

The obesity paradox: A further consideration in dialysis patients

Abstract: Several epidemiological cohorts have demonstrated that higher body mass index (BMI) is associated with lower mortality risk among patients receiving hemodialysis. However, BMI may be an inaccurate indicator of nutritional status among dialysis patients because it does not differentiate between muscle and fat mass or provide information about body fat distribution. More sophisticated methods of body composition analysis are therefore required to address the question of which component is associated with greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 48 publications
2
30
0
1
Order By: Relevance
“…Recent studies have suggested that metabolically unhealthy obesity and a visceral pattern of body fat deposition [3,29] are more important contributors to a risk assessment of mortality than the overall "body volume" as measured by the BMI. The WC, a representative marker of visceral body fat, was found to correlate with inflammation, whereas subcutaneous body fat may be an indicator of the nutritional status [30].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that metabolically unhealthy obesity and a visceral pattern of body fat deposition [3,29] are more important contributors to a risk assessment of mortality than the overall "body volume" as measured by the BMI. The WC, a representative marker of visceral body fat, was found to correlate with inflammation, whereas subcutaneous body fat may be an indicator of the nutritional status [30].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, measures of central or abdominal obesity, de ned by the WC and waist-hip ratio, have been used as more important predictors to assess the mortality risk than BMI [29,30]. WC, a representative marker of visceral body fat, was found to correlate with in ammation, whereas subcutaneous body fat may be an indicator of the nutritional status [31].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an obesity paradox was described in dialyzed patients [47][48]. It is associated with better survival of obese patients who were transplanted than all patients who stay on transplant waiting list.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with better survival of obese patients who were transplanted than all patients who stay on transplant waiting list. Howver these results may be confounded by worse outcome of malnourished ESKD patients [47,[49][50]. Moreover, obesity reduces the likelihood of being enrolled to the waiting list, but not the transplantation once enrolled, especially among women [17].…”
Section: Discussionmentioning
confidence: 99%